Sejarah Singkat Islamisasi di Tiongkok - Muliati, Muliati; Hidayah, Nur (Syams, 2023)
This article provides a comprehensive overview of the Islamization in Tiongkok, highlightingthree main aspects: the history of Islam in Tiongkok, the dynamics of Islam in Tiongkok,and the development of the Muslim community in Tiongkok. Historically, Islam enteredTiongkok in the 7th century through Arab and Persian merchants. The Chinese Muslimcommunity, known as the Hui, has existed for centuries and has become an integral part ofChinese society. Several Chinese dynasties, such as the Tang and Yuan dynasties, had strongIslamic influences and protected the rights of Muslims. In the dynamics of Islam inTiongkok, the article notes that Islam has experienced ups and downs, with periods oftension and intolerance, particularly during the Cultural Revolution. However, since thereform and opening-up of Tiongkok in the 1970s, religious life has improved, and Muslimshave more freedom. The Chinese government currently recognizes Islam as one of the officialreligions and seeks to maintain ethnic and religious stability. Meanwhile, the development ofthe Muslim community in Tiongkok shows that the Muslim population is estimated to be 23million, or around 1.8% of Tiongkok's total population. The Muslim community isscattered throughout Tiongkok, with the largest populations in Xinjiang, Ningxia, Gansu,and Qinghai. Chinese Muslims have contributed to Tiongkok's economic and socialdevelopment, but they also face challenges such as security issues, human rights, and culturalintegration. Overall, this article provides a comprehensive picture of the Islamization inTiongkok, tracing the history, dynamics, and development of the Chinese Muslimcommunity, which has become an integral part of Chinese society and economy.